METHODS OF SOLVING FINITE ISSUES OF APPLICATION OF NEWTON’S LAWS IN SCHOOL - Toxirova Maxfuzaxon Otaqo’ziyevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is devoted to the peculiarities of solving different types of applied problems in Physics in the system of general secondary education in the teaching of physics.